Bipolar Disorder with History of Physical Abuse and Comorbid Polycythemia Vera: a Case Report - Panjaitan, Endy Desmanto; Ida Aju Kusuma Wardani; I Gusti Ayu Indah Ardani (Faculty of Medicine, Universitas Airlangga, 2024)
Introductions: Based on a 2015 United Nations Children's Fund (UNICEF) report, violence against children is widespread in Indonesia; 40% of 13–15-year-old children reported being physically assaulted at least once a year, 26% reported being physically abused by a parent or caregiver, and 50% reported being bullied at school. Case: A 23-year-old female patient, Hindu, Balinese, unmarried, and unemployed, came alone to the psychiatric polyclinic of Wangaya Hospital. From history taking, there was dizziness, anhedonia, impaired attention, reduced self-esteem and confidence, guilt and uselessness, reference ideas, somatic delusions, relationship mood, logorrhea and flight of ideas, a history of mixed-type insomnia, and excessive energy. In a general examination, there were icteric sclera and palpable enlargement of the spleen (Schuffner 4). Neurological examination within normal limits. Discussion: The patient has bipolar disorder, caused by a traumatic experience in childhood. The patient was found to have a history of repeated treatment; she was initially diagnosed with bipolar disorder and received Depakote 250 mg and Clobazam 10 mg. Then, the patient came for treatment again at Wangaya Hospital on August 30, 2021, because of a headache and was diagnosed with bipolar affective disorder, with the current episode being moderately depressive with somatic symptoms. Conclusion: Traumatic childhood events are a risk factor for bipolar disorder. In addition to poor clinical presentation, the early onset of bipolar disorder is also an aggravating factor for symptom recurrence. Polycythemia vera can be a complicating factor in the recovery and relapse of bipolar disorder.